PENGARUH KUALITAS AUDITOR TERHADAP KUALITAS LAPORAN KEUANGAN PADA PERUSAHAAN PEMBIYAYAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2016 – 2020 - Eldi Puji Resza (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the effect of auditor quality on the quality of financial statements. The research method used is a quantitative research method with a descriptive and verification approach. The sample in this study were 8 financing companies that have been listed on the Indonesia Stock Exchange (IDX) in 2016 to 2020 as many as 40 observations of financial statement data and audit reports. The audit quality variable is proxied using the type of public accounting firm, while the quality of financial statements is proxied by using the return of equity, profit divided by equity. Hypothesis testing is done by using simple linear regression analysis method. The results of hypothesis testing give the result that the quality of auditors has a positive effect on the quality of financial statements 0.03 <0.05.